Phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha (PIK3CA)‐related overgrowth spectrum: A brief report. Issue 3 (1st March 2018) - Denorme, Pieter; Morren, Marie‐Anne; Hollants, Silke; Spaepen, Marijke; Suaer, Kate; Zutterman, Nele; Labarque, Veerle; Legius, Eric; Brems, Hilde
Abstract: A patient with extensive multisystem overgrowth caused by a somatic gain of function PIK3CA‐mutation is described. This case is an example of the clinical diversity of the PIK3CA‐Related Overgrowth Spectrum (PROS) as the patient had overlapping features of Congenital Lipomatous Overgrowth Vascular malformations Epidermal nevi and Skeletal abnormalities (CLOVES) syndrome and Megalencephaly‐Capillary malformation Polymicrogyria (MCAP) syndrome and underlines the utility of this umbrella term.